(untitled) (Research, Society and Development, 2022)
Introduction: Cardiotocography is the graphic record that evaluates fetal well-being, of great importance in questioning legal doctors. Computed cardiotocography came as an advance in order to reduce the subjectivity of tracing interpretation. The external form is most used, as it has non-invasive monitoring that reasonably records the accuracy of heart and fetal beats. The amount of contractions and fetal movements are also analyzed in this modality. Methodology: This is a descriptive qualitative study, defined by an integrative literature review, it is a relevant instrument in the communication of research results, as it provides a synthesis of the knowledge already produced and provides contributions to data production. Discussion: Cardiotocography (CTG) began its activity in the 1960s, seeking to assess fetal heart rate and uterine counteractivity at delivery. Its use was based on the principle of relativity of heartbeats, as it is one of the first changes to be observed in hypoxia situations. This evaluation seeks to assess the vitality of the conceptus during pregnancy and its main indication is to adjust actions that evolve with a higher risk of miscarriage, being more used in the final period of low-risk pregnancy. Conclusion: The cardiotocography tracing should be interpreted and analyzed according to the clinical picture presented by the patient, taking into account the stage of labor. The variations presented in the basal heart rate during labor, especially values of fall and tachycardia, or decelerations lasting longer than 60 seconds should cause greater concern on the part of the health professional.